Segregation texts: Riksdag's open data: Records of proceedings in the Chamber - Språkbanken Text (University of Gothenburg, 2024)
Records of proceedings in the Chamber

Protokoll från kammarens sammanträden
Segregationstexter: Riksdagens öppna data: Protokoll
Keywords: Language Technology (Computational Linguistics); corpus; Natural Language Processing; Språkbehandling och datorlingvistik